THE INTERRELATION OF LINGUISTICS AND LINGUOCULTUROLOGY - Ravshanova Mo'tabar (World Scientific Research Journal, 2025)
Annotation: In this article, the relationship between language and culture, linguistic and cultural units, cultural codes are expressed through proverbs and expressions used in Abdulla Qadiri’s novel “Bygone Days”,”Scorpion from The Altar”.